Networking China: The Digital Transformation of the Chinese Economy - Keane, Michael (2017)
Research on the Chinese Internet has led to a plethora of scholarly publications over the past two decades. Academic researchers outside of the Chinese mainland have mostly investigated political control and online activism whereas those within the mainland tend to enthuse about the benefits of technology for development. However, China’s rapidly growing communications landscape has received little attention internationally Networking China: The Digital Transformation of the Chinese Economy is a timely and ground breaking account of major transformations in China’s communications over the past two decades, with global warnings attached. The focus of the book is communications, comprising information and communication technologies (ICTs), telecommunications, and media.